Review of precision rice hill-drop drilling technology and machine for paddy - Zhang, Minghua; Wang, Zaiman; Luo, Xiwen; Zang, Ying; Yang, Wenwu; Xing, He; Wang, Baolong; Dai, Yizheng (International Journal of Agricultural and Biological Engineering, 2018)
Mechanized rice direct seeding is a cost-effective and efficient approach for rice cultivation. Recently, the use of rice direct seeding has been increasing rapidly owing to rural labour shortages and continuous increases in agricultural production costs. This article reviews the research and application progress of mechanized rice direct seeding including direct seeding technologies, precision rice seeding, precision rice seed-metering devices, key supporting agronomy technologies for mechanized rice direct seeding. South China Agricultural University developed precision rice hill-drop drilling (PRHDD) with synchronous furrowing and ridging technology and series machines for paddy that affords remarkable advantages in terms of saving time and labour, higher yield, and higher efficiency. In this approach, pre-germinated seeds are uniformly hill-dropped in the expected positions in puddled soil. It significantly improved the crop growth population and effectively solved the problems of high frequency of disease and pests caused by the irregular distribution of rice seeds with manual broadcasting, and generally reduces seed usage and increases the yield. Therefore, this technology has broad application prospects and great potential for promoting the development of mechanized rice direct seeding in China.Keywords: rice, precision rice seeder, hill-drop drilling for paddy rice, mechanical direct seedingDOI: 10.25165/j.ijabe.20181103.4249Citation: Zhang M H, Wang Z M, Luo X W, Zang Y, Yang W W, Xing H, et al. Review of precision rice hill-drop drilling technology and machine for paddy. Int J Agric & Biol Eng, 2018; 11(3): 1–11.